Banks' Acquisition of Private Information about Financial Misreporting - Chen, Po-Chang (The Accounting Review, 2016)
ABSTRACT This study investigates whether banks respond to financial misreporting as the borrowing firms release misstated financial reports, i.e., in the misreporting period. Drawing upon finance theory that recognizes banks' superior information access and processing abilities, this study predicts and finds that banks adjust loan contract terms in response to the ongoing misreporting. Compared with loans issued in the prior period, loans issued in the misreporting period have higher interest spread, are more likely to be secured by collateral, and have more restrictive covenants. Further analyses show that banks acquire indirect, rather than direct, information about the misreporting and that they do not fully adjust loan pricing until after the restatement announcement. Together, these findings suggest that banks make timely, but insufficient, adjustments during the misreporting period. Nevertheless, banks' early reactions appear to be unique, as equity investors do not respond to the ongoing misreporting, but react to the loan information when it becomes public. JEL Classifications: D82; G21; M41.